Poor R-wave progression and myocardial infarct size after anterior myocardial infarction in the coronary intervention era. (1st June 2015) - Kurisu, Satoshi; Iwasaki, Toshitaka; Watanabe, Noriaki; Ikenaga, Hiroki; Shimonaga, Takashi; Higaki, Tadanao; Ishibashi, Ken; Dohi, Yoshihiro; Fukuda, Yukihiro; Kihara, Yasuki
Abstract: Background: Regeneration of R-wave or disappearance of Q-wave sometimes occurs after myocardial infarction (MI) especially in the coronary intervention era. We assessed the impact of poor R-wave progression (PRWP) or residual R-wave in precordial leads on myocardial infarct size in patients with prior anterior MI treated with coronary intervention. Methods: Fifty-three patients with prior anterior MI and 20 age- and sex-matched patients without underwent electrocardiogram (ECG), myocardial perfusion single photon emission tomography (SPECT) and echocardiography. Poor R-wave progression (PRWP) was defined as RV3 ≤ 3 mm. Results: R-wave was significantly lower in all precordial leads in patients with prior anterior MI than those without. Among 53 patients with prior anterior MI, 33 patients had PRWP, and the remaining 20 patients did not. Patients with PRWP had larger sum of defect score (17.5 ± 8.6 vs 7.6 ± 10.3, p < 0.001) and lower left ventricular ejection fraction (LVEF) (46.1 ± 9.8% vs 55.2 ± 12.9%, p < 0.01) than those without. The sum of R-wave in lead V1 to V6 inversely correlated with the sum of defect score (r = − 0.56, p < 0.001), and positively correlated with LVEF (r = 0.45, p < 0.001). Conclusion: Our data suggested that residual R-wave during the follow-up period reflected myocardial infarct size and left ventricular systolic function well in patients with prior anterior MI treated with coronary intervention.